PENERAPAN BIOTEKNOLOGI DALAM EKSTRAKSI MINYAK KELAPA DENGAN MENGGUNAKAN KHAMIR ROTI (Saccharomyces cerevisiae) - Leta (Jurnal Matematika Sains dan Teknologi, 2009)
This research is aimed for knowing the influence of temperature, pH, and their interaction on the amount and quality of oils formed in fermentative extraction of coconut oil using bakers, yeast the treatment examined temperature divided into four treatments, pH divided into two treatments, and three repetitions. All treatment in this research met SII. The research result show that: (1) Treatment of temperatures give different effects on the amount of oils, temperatures of 350C and 300C produced the highest amount of oil, give different effects on water content, temperatures of 300C and 350C resulted in the lowest amount of water content, gave different effect on iodine number, and on lathering number, temperature of 350C resulted in the lowest number, did not give different effects on the level of free-fats acid. (2) Treatment of pH did not give different effect on the amount of oil, on water content but give different effect on iodine number, on lathering number, pH of 4 was lower the pH of 4.5. (3) Interaction of treatments of temperatures and pHs give different effect on the amount of oil, temperatures of 350C with pH of 4 and temperatures of 300C with pH 4 produced highest amount of oil, give different effect on water content, temperature of 300C with the pH of 4.5 resulted in the lowest amount of water content, the temperature of 250C with pH 4.5 produced high water content (0.55%), temperature 300C with pH 4.5 resulted in the lowest peroxide number. It gives different effect on the content of free fats acid, produced oil whit bright colour, good taste and smell and it was not immediately rancid.